Guía metodológica para mejorar la comunicación verbal en los niños de educación inicial. - González, Ana M. (2022)
Verbal language is a determining factor in people's education, since it allows people to communicate in order to improve their reality. The objective of this work is to compile strategies of stimulation through a methodological guide to improve verbal language in children of preschool education of three years old group of the UE. Cardenal Carlos María de la Torre. The research is framed in the quantitave approach, that is, qualitative and quantitative. The Descriptive Level is considered, because it details the relevant information related to verbal language in early ages. It is a Field Research because the information was obtained directly from the people involved in the investigation problem. To collect this information, the Language Subtest of the Psychomotor Development Test TEPSI was used, which indicates the level of language in the infants studied. To collect information from the 22 parents and 6 teachers, the survey technique was used with the questionnaire instrument. The contributions found are: The existence of language disorder in the studied children; The lack of knowledge of the educational responsibility and the feedback that families should provide to students; The teachers did not have a methodological guide that orients the stimulation of language in children and their families. As a conclusion we can say that the language disorders which would affect the student's student life, therefore early stimulation and family support are recommended to prevent and correct oral communication difficulties.